PEMENUHAN HAK MENDAPATKAN REMISI TERHADAP NARAPIDANA PENYALAHGUNAAN NARKOTIKA DI LEMBAGA PEMASYARAKATAN POHUWATO - Muhammad Rizal Lampatta; Agung A. Yusuf (TAHKIM, 2020)
epublic of Indonesia Law Number 12 of 1995 concerning Corrections has requested permission for fostered citizens. Penitentiaries allow approval for article 14 paragraph (1) Number 9. Granting remission rights for fostered residents, narcotics are not in accordance with other fostered citizens, therefore it needs to be asked. narcotics are classified as extraordinary crimes. In that case there are special requirements that must be resolved to get remission that is through good behavior, also must be a justice collaborator. This has been regulated in Republic of Indonesia Government Regulation Number 99 of 2012 concerning the Second Amendment to Republic of Indonesia Government Regulation Number 32 of 1999 concerning Provisions and Procedures for the Implementation of the Rights of Prisoners. Article 34 A. Pohuwato Penitentiary in granting remission has agreed to the provisions of the necessary legislation and must maintain that quality so as to provide remission to prisoners. Keywords: remission, inmate, recovering narcotics, correctional institution.